CLINICAL EVALUATION OF SIRAVEDHA IN THE MANAGEMENT OF GRIDHRASI WITH SPECIAL REFERENCE TO SCIATICA - Poonam, *Mohod; Sudesh, Gupta; Kirandeep, Kour (International Journal of Ayurveda and Pharma Research, 2015)
Gridhrasi (sciatica) is pain dominant lifestyle disorder, in which the pain starts from Sphik Pradesha (back region) and radiates towards the foot. According to Charaka it can be managed by the process of Siravedha, Snehana, Bastikarma and Agni karma. Siravedha is considered as half of the therapeutic measure in Shalyatantra like Basti in Kayachikitsa. Siravedha is an emergency management in Vataja nanatmaja vyadhi like Gridhrasi to achieve better results. It has been done at the site of four Angula above and below the Janu sandhi. The present study was carried out on clinical evaluation of Siravedha in Gridhrasi as cited by Sushruta in the context of management of Gridhrasi. For the study 15 patients were randomly selected from OPD and IPD of JIAR hospital, Jammu. It was single blind clinical study to evaluate the efficacy of Siravedha by subjective and objective criteria i.e. pain, pricking sensation, stiffness, tingling sensation, anorexia, torpor, heaviness, SLR angle and walking time. The study revealed that, there were significant results found in Gridhrasi by Siravedha. It destroyed the Avarana (obstruction) which helped in normal movement of Vata and therefore restored the normal circulation and function of Vata. Ultimately; it reduced pain, pricking sensation, stiffness, tingling sensation, heaviness and quick relief of symptoms. It was simple economical and highly effective procedure without producing any adverse effects.